Crystal Properties 4SO2Influence of Doping on K - A.Al- Dahair, Tariq; E.Al-Mahdawy, Maryam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Single crystals of pure and Cu+2,Fe+2 doped potassium sulfate were grown from aqueous solutions by the slow evaporation technique at room temperature. with dimension of (11x9 x4)mm3 and ( 10x 8x 5)mm3 for crystal doping with Cu &Fe respectively. The influence of doping on crystal growth and its structure revealed a change in their lattice parameters(a=7.479 Å ,b=10.079 Å ,c=5.772 Å)for pure and doping (a=9.687 Å, b=14.926 Å ,c= 9.125 Å) & (a=9.638 Å , b= 8.045 Å ,c=3.271 Å) for Cu & Fe respectively. Structure analysis of the grown crystals were obtained by X-Ray powder diffraction measurements. The diffraction patterns were analyzed by the Rietveld refinement method. Rietveld refinement plots for showing the experimental (red circles)calculated (black line) and difference profiles (blue line); green tick marks indicate reflection positions XRD measurements show the crystal system of orthorhombic.